Hafting with a Living Tree: A Historical Review of the Alleged Practice of Growth-Assisted Hafting. (3rd July 2021) - Arp, Don
ABSTRACT: Despite facing the challenges of preservation and rarity of evidence in the archaeological record, hafting methods are a research pursuit of archaeologists seeking to explain the construction of weapons and tools. Various works have included references to a unique method of hafting, referred to in this article as growth-assisted hafting, which involved inserting a stone into a living tree branch and waiting for wood growth to encase the inclusion before harvesting and constructing the knife, club or axe. Such a method would lack toolmarks and exhibit some evidence in wood grain patterns and possible abnormal fiber build-up of continued tree growth around the inclusion. This paper is a historical review of the alleged practice based on accounts from around the world and how the practice has re-appeared in the modern primitive skills subculture.